Aplikasi Analisis Wajah, Klasifikasi Gender dan Prediksi Usia Menggunakan Deep Learning pada Dataset Citra Wajah Manusia - Ch Angga Marcelio; Muhammad Adlan Azzikra; Dimas Putra Mufazzal; Aripili Rahman Illahi; Sulaiman Al Husain; Abdiansah Abdiansah (UNIVED Press, 2024)
Age and Gender Detection is a technology that utilizes artificial intelligence (AI) algorithms to identify and analyze the age and gender of a person through image capture as output. This technology provides automatic estimation of age and gender starting from detecting one or more objects (humans) and performing age and gender detection. The program uses pre-trained models and prototypes for face detection, age, and gender, resulting from training processes using deep learning techniques. By using these models and prototypes, the program can efficiently analyze each face found in images or videos and provide age and gender estimates with reliable accuracy. The main purpose of the Age and Gender Detection Application is to provide accurate and useful information about the age and gender of individuals based on the input images, becoming an efficient solution in image processing and artificial intelligence fields for various application contexts requiring facial data analysis.